Mechanical characteristics of circular elastomeric hollow rubber bearing - Adnan, Azlan; Sunaryati, Jati (2006)
The isolation system reduces the effect of the horizontal components of the ground acceleration by interposing structural elements with low horizontal stiffness between the structure and the foundation. This gives the structure a fundamental frequency that is much lower than both its fixed-base frequency and the predominant frequencies of the ground motion. The isolation system does not absorb the earthquake energy, but deflects it through the dynamics of the system. One of these devices of isolator appears as the laminated rubber bearing. Structural Earthquake Engineering Research (SEER) has been developing the hollow base isolator in order to reduce the horizontal stiffness of the isolator and to increase the effectiveness of the conventional one. Finite element models were studied the mechanic behaviour of elastomeric bearing under compressions and shear loads. The previous programs assumed the isolator as an elastic material. In contrast, the isolator is made from elastomeric rubber bearing which is not an elastic material. Therefore, the previous programs should be clarified or modified to obtain more reliable results.